The Code Mixing in the Classroom Conversation of First Semester Students of University of HKBP Nommensen Pematangsiantar - Leonita Maria Efipanias Manihuruk (Medan Resource Center, 2021)
This thesis is an analysis on the code mixing of students’conversation in the classroom. Code mixing occurs when a word or an utterances from element language A is mixed into the language context of language B. Caused by the globalization of technology nowadays, many people tend to mix their language, especially Indonesian to English language in their conversations. So the problems formulated in this thesis are “what are the types of code mixing used by the first semester students of University of HKBP Nommensen Pematangsiantar in their conversation in the classroom, and what is the dominant code mixing used by the first semester students of University of HKBP Nommensen Pematangsiantar in their conversation in the classroom?” This research is a descriptive qualitative research because the collected data and the result of data analysis are in the form of sentences. The instrument in collecting the data is record and documentative technique. The data collected in this thesis is the recording of code mixing in the students’conversations. The data were analyzed based on Hoffman’s theory. The result of this research that there are three types of code mixing found in students’conversation in the classroom. They are : intra-sentential code mixing, intra-lexical of code mixing, and involving a change of pronunciation. Totally, there are 25 code mixing and 10 conversations representing code mixing. The percentage of intra-sentential code mixing is 24%, intra-lexical code mixing is 68%, and involving a change of pronunciation is 8%. From the percentage above, it can be concluded that intra-lexical code mixing is the most dominant code mixing used by first semester students of University of HKBP Nommensen Pematangsiantar in their conversation in the classroom. The findings implies that the code mixing is being accepted by the students as an important aspect variety of language in society.